TINJAUAN YURIDIS TENTANG PERJANJIAN KERJASAMA ANTARA PT. SUMALINDO LESTARI JAYA GLOBAL TBK SAMARINDA DENGAN KARYAWAN - Nasrun Tulalan (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
AbstactThis scientific paper is a result of research as a final project in the completion of studies at the Faculty of Law of the University of August 17, 1945 Samarinda, this scientific paper is entitled Juridical Review of the Cooperation Agreement between PT. Sumalindo Lestari Jaya Global Tbk Samarinda with Employees.This scientific writing uses a descriptive analysis research method, which is a form of research that describes the situation or situation accompanied by an estimate of data and information obtained in relation to the problem under study, for further analysis.In the context of increasing national development in general and in particular in the context of improving the welfare of workers / workers, especially in PT. Sumalindo Lestari Jaya Global Tbk Samarinda, a cooperation agreement between workers and employers is needed. With the existence of the Serikat Buruh Borneo Indonesia (SBBI) as a representative of employees, aspirations and desires can be well targeted delivered between employees and the company. Work agreements based on the Pancasila industry while still guided by Law No. 22 of 1957 concerning the settlement of labor disputes adhere to a principle of deliberation to reach consensus by grounding in the first stage if a dispute is settled, the settlement is left to the disputing parties. This can eliminate disputes and obstacles that exist in the implementation of Law number 21 of 1954 concerning Labor Agreements between trade unions and employers, in this case the company PT. Sumalindo Lestari Jaya Global Tbk Samarinda.